EFEK AKUT LATIHAN SENAM PERSADIA 1 TERHADAP KADAR MALONDIALDEHYDE DAN KADAR CREATINE KINASE - Pratama, Yuan Guruh; S, Gadis Meinar; Purwanto, Bambang (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Diabetes dance of Persadia 1 is one Physical activity in sports involving muscle contraction especially in eccentric contractions will potentially increase malondialdehyde and creatine kinase serum levels. The aim of this study was to determine the effect acute exercise Diabetes Dance of Persadia 1 on malondialdehyde and creatine kinase serum levels. This research was experimental fields with pretest – posttest control group design. Malondialdehyde serum lavels were measured using TBARS, while creatine kinase serum levels using ELISA. Paired – t test shows there was a significant decrease in MDA (p = 0,006) and CK (p = 0,033) serum levels, but from the results of the difference test between groups showed no significant differences between treatment group (p = 0,163) control group (p = 0,137). We can conclude there was a decrease in malondialdehyde and creatine kinase serum levels after being given Diabetes Dance of Persadia 1, but did not show significant differences between treatment and control group if only given onetime Diabetes Dance of Persadia 1 exercise.